Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s13256-018-1783-z
|View full text |Cite
|
Sign up to set email alerts
|

Huge chronic expanding hematoma of the iliac bone following multiple hip surgeries: a case report

Abstract: BackgroundChronic expanding hematoma is a rare entity resulting from trauma or surgery. This condition usually occurs in soft tissue, such as the trunk or extremities, while chronic expanding hematoma arising from bone has not been reported previously. We describe an unusual case of a huge intraosseous chronic expanding hematoma arising from the ilium, which had grown over a 40-year period following hip surgeries.Case presentationA 57-year-old Japanese woman presented with a 1.5-year history of right hip pain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This is the first reported case of a large intraosseous CEH that presented with chronic DIC and occurred 22 years after THA; it was successfully treated with a single-stage excision and revision THA. In 2018, Morishita et al [3] first reported a case of a rare complication wherein a CEH arose from the iliac bone following a hip surgery. To the best of our knowledge, this is the only other reported case of an intraosseous CEH.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first reported case of a large intraosseous CEH that presented with chronic DIC and occurred 22 years after THA; it was successfully treated with a single-stage excision and revision THA. In 2018, Morishita et al [3] first reported a case of a rare complication wherein a CEH arose from the iliac bone following a hip surgery. To the best of our knowledge, this is the only other reported case of an intraosseous CEH.…”
Section: Discussionmentioning
confidence: 99%
“…Certain stimuli, such as trauma and surgery, are related to the development of CEH [ 5 , 7 , 8 ]. In fact, some rare cases of surgery-related CEH have been reported [ 5 , 9 , 10 ]. Therefore, CEH can theoretically occur anywhere in the body.…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases, a hematoma may slowly increase in size after an initial hemorrhagic event, referred to as a chronic expanding hematoma ( CEH ) [ 1 ]. CEH can develop in any body region [ [2] , [3] , [4] ] and is often difficult to distinguish from malignant tumors because of its large size and slow progressive enlargement [ 5 ]. Herein, we present a relatively rare case of intrathoracic CEH after thoracic surgery for lung cancer more than 20 years prior and describe its radiological features in detail.…”
Section: Introductionmentioning
confidence: 99%